PENGEMBANGAN E-MODUL PADA MATA PELAJARAN DESAIN GRAFIS PERCETAKAN SISWA KELAS XI MULTIMEDIA DI SMKN 1 KERINCI - Wenti Julia Analismi; Heri Mulyono; Rini Novita (Universitas Muhammadiyah Tapanuli Selatan, 2023)
There are obstacles experienced in the learning process, such as a shortage of teaching materials in the form of textbooks and limited use of computer media to convey material, and the development of learning resources such as modules has not been carried out. To create a learning atmosphere that is not boring, it is necessary to carry out the latest innovations, namely the development of E-Module learning media. The type of research used is Research and Development (R&D) by adopting the ADDIE model which consists of 5 stages namely (Analyze, Design, Development, Implementation, Evaluation). Data collection methods are taken from observation, questionnaires and documentation. This study aims to determine the practicality and validity of the product being developed. The average percentage (%) of the validity of the E-Module using the Canva application is 92.89% with a very valid category. This can be confirmed from all aspects that have been assessed by the validator. While the practicality of the percentage of E-Module Development using the Canva application is 88.67% in the very practical category. In other words, E-Module development using the Canva application is very practical in learning Printing Graphic Design.